Shear Performance of Reinforced Shear Pocket Joint in Light Steel—Recycled Concrete Composite Floor - Jinliang Bian; Jingwei Zhang; Lidong Zhao; Wei Gan; Wanlin Cao (Buildings)
To address the challenges of slow construction and high self-weight in steel–concrete composite floors for rural light steel frame structures in China, a new prefabricated floor system was developed. This system features prefabricated slabs made from recycled concrete, connected via reinforced shear pocket joints. In seismic environments, assembly floor joints often become vulnerable points, making their shear resistance particularly crucial. This study investigated the shear performance of this new type of floor joint, examining the effects of various parameters such as joint configuration, stud diameter, recycled concrete strength, and grout strength. A refined finite element model was established for an in-depth parameter analysis. The research revealed stud–shear failure as the mode of floor joint failure under different design parameters. The detailed design of the new joint structure ensures safety in the floor joint area. Increasing stud diameter, recycled concrete strength, and grout strength all contributed to enhancing the joint’s shear capacity and stiffness, with stud diameter having the most significant impact. Higher recycled concrete strength improved shear capacity, although its influence decreased beyond a certain threshold. Optimal reserved hole diameter proved beneficial for enhancing joint shear performance, with a diameter of 40 mm showing superior performance.